2013
DOI: 10.1103/physreve.87.012501
|View full text |Cite
|
Sign up to set email alerts
|

Apparent viscosity ofp-methoxybenzylidene-p-n-butylaniline in the presence of electrohydrodynamic convection

Abstract: The apparent shear viscosity of p-methoxybenzylidene-p -n-butylaniline in the presence of electrohydrodynamic convection (EHC) is investigated experimentally. In the absence of an electric field, directors are almost aligned along the flow direction such that the viscosity is close to the minimum of the Miesowicz viscosities. Since EHC disturbs the flow-aligned director configuration, the viscosity increases as the applied voltage is increased in the low-voltage regime. In the high-voltage regime, however, fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recently, Nagaya et al demonstrated a remarkable reduction of viscosity in a nematic liquid crystal (NLC) [15,16]. Typical NLCs consist of rodlike molecules with longrange orientational order, where the average direction of the molecules is designated by a unit vector n that is referred to as the director [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nagaya et al demonstrated a remarkable reduction of viscosity in a nematic liquid crystal (NLC) [15,16]. Typical NLCs consist of rodlike molecules with longrange orientational order, where the average direction of the molecules is designated by a unit vector n that is referred to as the director [17,18].…”
Section: Introductionmentioning
confidence: 99%